SOROPREVALÊNCIA DE ANTICORPOS “ANTI-ARBOVÍRUS” DE IMPORTÂNCIA EM SAÚDE PÚBLICA EM AVES SELVAGENS, BRASIL – 2007 E 2008 - Francisco Anilton Alves Araujo; Pedro Cerqueira Lima; Maria Auxiliadora Andrade; Valéria De Sá Jayme; Daniel Garkauskas Ramos; Silvio Lucena da Silveira (Universidade Federal de Goiás, 2012)
The objective of this study was to determine the prevalence of hemagglutination-inhibition antibodies against arboviruses in wild birds in two serological surveys conducted in Salinopólis/Para State. A total of 544 birds of 17 species were captured, being nine resident and eight migratory. Blood was collected from 350 birds for virus isolation, but no virus was isolated. Of the 95 sera in which the hemagglutination inhibition test was performed, 14.7% were reactive to alphavirus, 9.5% to flavivirus and 7.4% to bunyavirus. Of the positive reactions, 84.9% occurred in migratory birds and 15.1% i resident birds. The proportions of positive reactions to the test among migratory and resident birds were 31.5% and 18.2%, respectively, which was not statistically different (p> 0.05). For alphaviruses, the species Pluvialis squatarola showed 28.6% positivity, followed by 11.8% in Arenaria interpres. For flaviviruses, only the species Sterna superciliares and Calidris pusilla were reactive to the hemagglutination inhibition test. Regarding the bunyavírus, the Arenaria interpres was 5.9% positive for the Oropouche virus. Migratory birds have proved to be important amplifiers of the arboviruses surveyed, although no viruses were isolated. Some bird species have greater amplification capacity of certain arboviruses than others. Virus isolation in wild birds is difficult, in view of the need of blood sampling in animals within the viremic period.